Evaluating the risk of knee osteoarthritis following unilateral ACL reconstruction based on an EMG-assisted method - Long, Ting; Fernandez, Justin; Liu, Hui; Li, Hanjun (Frontiers in Physiology, 2023)
Objective: Anterior cruciate ligament reconstruction (ACLR) cannot decrease the risk of knee osteoarthritis after anterior cruciate ligament rupture, and tibial contact force is associated with the development of knee osteoarthritis. The purpose of this study was to compare the difference in bilateral tibial contact force for patients with unilateral ACLR during walking and jogging based on an EMG-assisted method in order to evaluate the risk of knee osteoarthritis following unilateral ACLR. Methods: Seven unilateral ACLR patients participated in experiments. The 14-camera motion capture system, 3-Dimension force plate, and wireless EMG test system were used to collect the participants' kinematics, kinetics, and EMG data during walking and jogging. A personalized neuromusculoskeletal model was established by combining scaling and calibration optimization. The inverse kinematics and inverse dynamics algorithms were used to calculate the joint angle and joint net moment. The EMG-assisted model was used to calculate the muscle force. On this basis, the contact force of the knee joint was analyzed, and the tibial contact force was obtained. The paired sample t-test was used to analyze the difference between the participants’ healthy and surgical sides of the participants. Results: During jogging, the peak tibial compression force on the healthy side was higher than on the surgical side (P=0.039). At the peak moment of tibial compression force, the muscle force of the rectus femoris (P=0.035) and vastus medialis (P=0.036) on the healthy side was significantly higher than that on the surgical side; the knee flexion (P=0.042) and ankle dorsiflexion (P=0.046) angle on the healthy side was higher than that on the surgical side. There was no significant difference in the first (P=0.122) and second (P=0.445) peak tibial compression forces during walking between the healthy and surgical sides. Conclusion: Patients with unilateral ACLR showed smaller tibial compression force on the surgical side than on the healthy side during jogging. The main reason for this may be the insufficient exertion of the rectus femoris and vastus medialis.